Students’ Difficulties in Reading Comprehension at the Ninth Grade MTs Negeri 1 Manado - Kaharuddin, Nikmala N; Thaib, Dhea Ramadanti (Institut Agama Islam Negeri (IAIN) Manado, 2023)
This research aims to identify the difficulties faced by students in reading and thecauses of these difficulties. The researcher employed a mixed-methods research(MMR) approach, utilizing four research instruments: observation, interviews, tests,and documentation. The sample for this research consisted of 30 students from class9-C and two English teachers from class 9 of MTs Negeri 1 Manado. There were threedata collection procedures. The first procedure involved the researcher observingclass 9-C. The second procedure included the administration of a multiple-choice testwith 10 questions to the students of class 9-C. The third procedure involvedconducting interviews with 30 students and 2 English teachers regarding the causesof students' difficulties in reading. Based on the research findings, the researcheridentified four difficulties that students face in understanding reading: limitedvocabulary with a percentage of 68.33%, drawing conclusions 60%, detailscomprehension 54.16%, and grasping the main idea 50%. There were two factorscausing students' difficulties: internal factors and external factors. Internal factorsincluded students not reading enough, texts in English, limited vocabulary, andstudent laziness. External factors included a lack of English books and students notbringing dictionaries.Keywords: Student difficulties, Reading comprehension, Internal and External Factor